Chicago Católico : Making Catholic Parishes Mexican - Kanter, Deborah Ellen (Book collections on Project MUSE., 2020)
"Prior to 1960, Mexican Catholics in Chicago could only attend Spanish-language mass at three churches; now nearly 100 area churches offer mass in Spanish, to congregations that are nearly half Mexican and Latino. The third largest archdiocese in the United States has, in many ways, become "Chicago católico," a place where Mexican devotions hold sway well beyond church doors. Deborah E. Kanter uses the Catholic parish in Chicago to investigate Mexican immigration and transformation. Beginning in the 1920s, two parishes consciously built sites of Mexican identity, serving as both refugio and centers of community life. For individuals arriving from Mexico, these parishes had an Americanizing influence, while Mexican-American laypeople gained a sense of mexicanidad by participating in parish religious and social events. Mexicans fiercely attached themselves to specific parishes, much like other ethnic groups in days gone by. But as the city changed around them, Chicago's expanding Mexican Catholic population re-shaped not only these parishes but entire neighborhoods. For example, in the Near West Side neighborhood, Mexican immigrants congregated at St. Francis of Assisi, until its parishioners were uprooted for the construction of the University of Illinois Chicago campus. Many of St. Francis's congregates moved to Pilsen, which became Chicago's first majority Mexican neighborhood by 1970. Like the parishes on the Near West Side decades before, Pilsen's parishes reimagined their community identity, even as a new tide of Mexican immigrants in the 1960s challenged Euro-American and Mexican-American parishioners alike. Written to engage a wider readership than a typical scholarly monograph, Kanters limits the use of academic jargon and engaged scholarly debates more implicitly than explicitly. Apt for classroom adoption, the book also has potential to reach a non-academic readership especially among avid readers of Catholic, Chicago, and Latino topics"--